Feminism and the Making of Canadian Working-Class History: Exploring the Past, Present and Future - Sangster, Joan (Labour / Le Travail, 2000)
This paper explores the writing of women's labour history in Canada over the last thirty years. Three interconnected forces have shaped the contours of this intellectual production: the course of feminist, Left, and labour organizing; trends in international social theory; and directions in Canadian historiography. Feminist challenges to the initially 'masculinist' shape of working-class history, along with more recent calls to integrate race and ethnicity as categories of analysis, have produced important shifts in the overall narrative of Canadian working-class history and in the dominant paradigms used to examine labour. As a result, gender has been more effectively, though certainly not completely, integrated into our analysis of class formation. More recent post-structuralist theoretical trends, along with the decline of the Left and labour militancy, have called into question some fundamental suppositions of women's and working-class history, creating an unsettled and uncertain future for a feminist and materialist exposition of class formation in Canada.